A Juridical Analysis of Human Trafficking as a Transnational Crime from the Perspective of International Criminal Law and Its Implementation in Indonesia - Jeli Yanti; Wevy Efticha Sary (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Human trafficking constitutes one of the most serious and systematic forms of transnational crime in the era of globalization. Indonesia, as a country of origin, transit, and destination for human trafficking, faces complex challenges in enforcing international criminal law. This study aims to normatively analyze the legal position of human trafficking as a transnational crime from the perspective of international criminal law, while evaluating the effectiveness of the implementation of Law Number 21 of 2007 on the Eradication of the Crime of Trafficking in Persons in Indonesia. Employing a statute approach and a conceptual approach, this study finds a significant gap between international legal norms as stipulated in the Palermo Protocol 2000 and Indonesia's domestic regulations, particularly regarding the definition of victims, recovery mechanisms, and inter-agency coordination. The novelty of this research lies in the identification of three structural weaknesses in the implementation of the Anti-Trafficking Law: (1) normative ambiguity in defining exploitation; (2) weak restitution and compensation mechanisms for victims; and (3) institutional misalignment between central and regional Anti-Trafficking Task Forces. This study recommends a partial revision of the Anti-Trafficking Law and strengthening of vertical-horizontal coordination among law enforcement agencies.